Persepsi Mahasiswa terhadap Penerapan Pendekatan Deep Learning dalam Transformasi Kurikulum Abad 21 - Wikan Budi Utami; Nita Elisa Damayanti; Fikri Aulia; Alfredo Hagus Setiawan; Benjamin Laurentino Vaz (Wacana Akademika: Majalah Ilmiah Kependidikan, 2025)
his study employed a quantitative approach with a descriptive method. Its objective was to systematically and objectively describe students' perceptions of the deep learning approach in the context of 21st-century education. The subjects of this research were 43 undergraduate students from the Education Department in Malang, class of 2022, selected through purposive sampling, specifically those who had taken the Curriculum and Instruction course.The study revealed that the perceptions of these undergraduate education students in Malang toward the deep learning approach in the 21st century were still at a moderate level. Some students expressed interest in and support for the deep learning approach, citing its relevance to technological advancements, digital literacy demands, and the need to improve the quality of learning. However, the students’ understanding of the deep learning concept remained weak. Many had not yet been introduced to or deeply understood the approach, both in terms of its foundational principles and its practical implementation in learning contexts.Students recognized that the deep learning approach requires critical thinking skills, reflective abilities, and sensitivity to student character diversity. They viewed the deep learning approach as capable of fostering more meaningful, personalized, and adaptive learning experiences tailored to students' needs.